Kualifikasi Kedewasaan Iman Dalam Pernikahan Kristen Untuk Meminimalkan Perceraian - Laoli, Hasrat; Wibowo, Moses (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
Marriage is an institution that is considered sacred and essential in various faiths, including in the Christian perspective. However, the phenomenon of divorce is still a reality faced by many married couples. This phenomenon raises questions about the elements that influence the sustainability of marriage. This study offers a Christian perspective to minimize divorce by highlighting the importance of the maturity qualification of faith in Christian marriage. Through a literature study focusing on description, this article analyzes the relationship between the maturity of faith and Christian marriage and the protective factors of marriage against divorce. The findings show that the maturity of faith plays an essential role in building a strong marriage relationship. The implication of this paper is the importance of developing faith maturity in nurturing Christian marriage relationships as a preventive measure against divorce.